Good results at 2-year follow-up of a custom-made triflange acetabular component for large acetabular defects and pelvic discontinuity: a prospective case series of 50 hips. (4th May 2021) - Scharff-Baauw, Marieke; Van Hooff, Miranda L; Van Hellemondt, Gijs G; Jutte, Paul C; Bulstra, Sjoerd K; Spruit, Maarten
Abstract : Background and purpose — Custom triflange acetabular components (CTACs) are suggested as good solutions for large acetabular defects in revision total hip arthroplasty. However, high complication rates have been reported and most studies are of limited quality. This prospective study evaluates the performance of a CTAC in patients with large acetabular defects including pelvic discontinuity. Patients and methods — Prospectively collected data of 49 consecutive patients (50 hips), who underwent an acetabular revision with a CTAC were analyzed. Follow-up (FU) was 2 years. The median age of the patients was 68 years (41–89) and 41 were women. Primary outcomes were re-revision of the CTAC and differences between the modified Oxford Hip Score (mOHS) preoperatively and at 2-year follow-up. Secondary outcomes included several patient-reported outcomes (PROMs), radiological results, complications, and a comparison between hips with and without pelvic discontinuity (PD). Results — 1 patient (1 hip) was lost to the 2-year FU. No CTAC needed re-revision. The preoperative and 2-year FU mOHS were available in 40 hips and improved statistically significantly. All of the other secondary outcomes improved over time. 5 hips (of 45 with radiological 2-year FU) had loosening of screws. 8 hips had complications, including 3 persistent wound leakage, 3 pelvic fractures, and 1 dislocation. The mOHS and complication rate were similar in hips with and without PD. Interpretation — Reconstruction of large acetabular defects with and without PD with this CTAC showed good improvement in patient-reported daily functioning, high patient-reported satisfaction, few complications, and no re-revisions at 2-year FU.